The risk-return trade-off in human capital investment - Charlotte Christiansen; Juanna Schrøter Joensen; Helena Skyt Nielsen (Institute for the Study of Labor (IZA), 2006)
In this paper we analyze investments in human capital assets in a way which is standard for financial assets, but not (yet) for human capital assets. We study mean-variance plots of human capital assets. We compare the properties of human capital returns using a performance measure and by using tests for mean-variance spanning. A risk-return trade-off is revealed, which is not only related to the length of education but also to the type of education. We identify a range of educations that are efficient in terms of investment goods, and a range of educations that are inefficient, and may be chosen for consumption purposes.
Keywords: I21; J24; 330; educational choice; efficient frontier; human capital investment; mean-variance analysis; Humankapital; Bildungsinvestition; Bildungsverhalten; Rendite; Bildungsertrag; Risiko